Przedsiębiorczość pozytywna – przyczyny i rezultaty przedsiębiorczości z zakresu pozytywnej teorii organizacji - Przemysław Zbierowski (Problemy Zarządzania, 2015)
The paper attempts to conceptualize a new approach in entrepreneurship research – positive entrepreneurship. It involves adapting or narrowing positive organizational scholarship to the field of entrepreneurship. More specifically, the paper presents positive phenomena that are antecedents and outcomes of the process of entrepreneurship. Among antecedents, psychological capital, pro-social motivation and creativity are discussed. The outcomes comprise psychological well-being, job satisfaction and worklife balance. The paper also presents the results of preliminary research on the well-being of various categories of entrepreneurs conducted as part of the Global Entrepreneurship Monitor. The paper opens a new research notion and is concluded with the propositions of research questions.